2014
DOI: 10.2460/javma.244.2.170
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of acute lung injury in dogs receiving transfusions

Abstract: VetALI occurred in dogs that received transfusions at a frequency similar to that previously reported for ARDS in ill dogs that did not receive transfusions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
33
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(34 citation statements)
references
References 16 publications
1
33
0
Order By: Relevance
“…TRALI is suspected in dogs and has a higher incidence in human patients after FFP than other blood products but has not been confirmed to occur in cats. 28 Suspicion for TRALI was not noted in the medical records of this population.…”
Section: Discussionmentioning
confidence: 79%
“…TRALI is suspected in dogs and has a higher incidence in human patients after FFP than other blood products but has not been confirmed to occur in cats. 28 Suspicion for TRALI was not noted in the medical records of this population.…”
Section: Discussionmentioning
confidence: 79%
“…Increases in circulating NET biomarkers in TRALI human patients' blood and presence of NETs in the alveoli of mice and people with TRALI suggest there could be a key role for NETs in TRALI pathogenesis 12,13 . Although the incidence of TRALI in veterinary medicine is likely much lower than it is in human medicine 32 or might not occur at all, 1 the proinflammatory nature of NETs makes them likely players in other transfusion reactions as well 9‐11 . Transfusion of NLR RBC to healthy dogs induces significant inflammation which is eliminated by LR of the RBC units before storage 4 .…”
Section: Discussionmentioning
confidence: 99%
“…There was no difference in severity of illness between the transfused and nontransfused groups based on acute physiology and chronic health evaluation (APACHE) III scores. A recent prospective study of 54 dogs receiving transfusions of any type reported that 2/54 were suspected to have developed veterinary acute lung injury (VetALI) based on a PaO 2 :FiO 2 ratio < 300, post transfusion development of radiographic pulmonary infiltrates, or development of respiratory compromise . However, as these 2 patients had underlying diseases that already predisposed them for the development of ALI, the role that transfusion played in the development of ALI is unclear …”
Section: Introductionmentioning
confidence: 99%